Effect of alcoholic extracts of millet seed (Panicum miliaceum L.) on spatial memory in male mice - Masoud Motabar Rody; Maryam Tehranipour; Nastaran Amintaheri (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Learning is the acquisition of information that makes this possible, and memory is meant to store this information. Millet contains proteins, minerals, vitamins and antioxidants needed to preserve the life and health of mammalian cells. This study was conducted to determine the effect of alcoholic extracts of seed of millet (Panicum miliaceum L.) on spatial memory in mice. Methods: In this experimental study, 24 male rats were randomly allocated into 4 groups. Hydrochloric extract of Prossu millet was prepared by Soxhlet method and injected into three treatment groups with doses of 25, 50 and 75 mg/kg/bw by intraperitoneal injection for 21 days. Animals in control group were received normal saline. After one month from the first injection, learning behaviors and memory tests were performed. Mauritius water maze was used to evaluate the spatial memory. Also, shuttle box method was used to determine passive avoidance of spatial memory. Results: The results showed that the mean time for finding the platform between the control group and alcoholic treatments in doses of (75 mg/kg/bw) was significantly different (P<0.05). Also, the mean time of training and test time in control and treatment groups receiving alcoholic extract showed a significant difference, indicating that this extract had a significant effect. Conclusion: Alcoholic extract of millet seed with dosage of 75 mg/kg/bw improves the learning and spatial memory of male mice.